Sports Broadcasting - Hull, Kevin (Human Kinetics Library, 2022)
With the thrill of the game and the excitement of documenting captivating moments for sports history, sports broadcasting is one of the most desired jobs among sports and journalism professionals. Designed to provide students with the skills to be successful in their careers, Sports Broadcasting is a comprehensive look at the field, with coverage of all aspects of the job that an entry-level sports broadcaster will need to know about. The text begins with the history and background of the sports broadcasting industry. Students will next learn about modern topics that are critical in the business today, with an overview of the various outlets, including television, radio, streaming, and podcasting. They will then dive into lessons on the skills every sportscaster needs for success, including conducting in-person and remote interviews of coaches and players, writing for broadcast versus writing for other channels such as web and mobile devices, shooting games or events, producing a sportscast, and editing video for broadcast. The career demands of both television and radio broadcasting are explored, and the increasing popularity of podcasting and streaming is examined. Students will journey through the steps involved in preparing for a live sports production, including play-by-play for radio and television, color commentary, and sideline reporting. A look into the different types of social media and their impact on sports broadcasting is followed by tips and advice on creating an effective social media presence and best practices for using social media as a sports broadcaster. The final chapters prepare students to pursue a career in sports broadcasting—offering practical advice on preparing resumes, portfolios, and job searching—and discuss issues and ethics relevant to modern-day sports broadcasting. Throughout the text, Major Moments sidebars discuss defining moments in the history of sports broadcasting and their impact on the field today, while Pro Advice sidebars feature interviews with sports broadcasting professionals and offer career tips and practical advice. With Sports Broadcasting, students will gain the knowledge and practical skills they need to be a well-rounded broadcaster in any segment of the field